A holistic framework for development and assessment of risk‐informed performance‐based building regulation. (3rd November 2020) - Meacham, Brian J.; Stromgren, Michael; van Hees, Patrick
SUMMARY: Fire safety provisions in building regulation are about managing risk. In order to appropriately characterize and incorporate risk measures into building regulation, it is helpful to view building regulatory systems (BRS) as complex socio‐technical systems (STS), wherein there are interactions between institutions, technology and people, which ideally work together to mitigate risk to a societally tolerable level. A description of BRS as STS and how to assess the efficacy of the BRS in managing fire risk is presented. To illustrate how STS concepts can be used to evaluate and restructure a functional‐ or performance‐based BRS, STS concepts are applied to the evaluation of the building regulatory system in England.